Variability in Basal Melting Beneath Pine Island Ice Shelf on Weekly to Monthly Timescales. Issue 11 (28th November 2018) - Davis, Peter E. D.; Jenkins, Adrian; Nicholls, Keith W.; Brennan, Paul V.; Abrahamsen, E. Povl; Heywood, Karen J.; Dutrieux, Pierre; Cho, Kyoung‐Ho; Kim, Tae‐Wan
Abstract: Ocean‐driven basal melting of Amundsen Sea ice shelves has triggered acceleration, thinning, and grounding line retreat on many West Antarctic outlet glaciers. Here we present the first year‐long (2014) record of basal melt rate at sub‐weekly resolution from a location on the outer Pine Island Ice Shelf. Adjustment of the upper thermocline to local wind forced variability in the vertical Ekman velocity is the dominant control on basal melting at weekly to monthly timescales. Atmosphere‐ice‐ocean surface heat fluxes or changes in advection of modified Circumpolar Deep Water play no discernible role at these timescales. We propose that during other years, a deepening of the thermocline in Pine Island Bay driven by longer timescale processes may have suppressed the impact of local wind forcing on high‐frequency upper thermocline height variability and basal melting. This highlights the complex interplay between the different processes and their timescales that set the basal melt rate beneath Pine Island Ice Shelf. Plain Language Summary: Ice shelves—the floating extensions of the Antarctic ice sheet—are melted from beneath when in contact with warm ocean waters. The rate at which they melt is especially important for controlling Antarctica's contribution to future sea level rise, and extreme basal melting may even be capable of causing the West Antarctic Ice Sheet to rapidly collapse. Here we use the first high resolution time series of basal melting observed beneath Pine Island Ice Shelf in the Amundsen Sea sector of West Antarctica to explore what sets the melt rate on short timescales. We find that during 2014, the local wind patterns are particularly important, as they are capable of changing the ocean temperature beneath Pine Island Ice Shelf. In other years, however, local wind patterns seem less important, highlighting the complex interactions that exist between the ice shelf and the ocean upon which it floats. Key Points: Basal melting at a single location beneath the outer Pine Island Ice Shelf is highly variable on weekly to monthly timescales throughout 2014 Adjustment of the upper thermocline to local wind forcing is the dominant control on this short timescale variability When longer timescale processes drive a deeper thermocline in Pine Island Bay, wind‐forced high‐frequency variability in the basal melt rate appears to be suppressed